Pengaruh Kesadaran Wajib Pajak,Pelayanan Perpajakan Dan Pengetahuan Wajib Pajak Terhadap Penerimaan Pajak Pada KPP Pratama Jambi Telanaipuara. - yenti; Elyanti Rosmanidar; Marissa Putriana (Jurnal Mutiara Ilmu Akuntansi, 2023)
This study aims to determine the effect of taxpayer awareness, tax services and knowledge at the Primary Tax Service Office (KPP) Jambi Pratama. TPB). The population in this study includes individual taxpayers who are registered at the Jambi Telanaipura Pratama Tax Office with a total of 230,533 taxpayers. The number of samples used in this study were 100 respondents with the technique of determining the sample using the Probability Sampling method. Data collection was carried out using the questionnaire method. The data analysis technique used is multiple linear regression analysis. The results of the study show that taxpayer awareness, tax services and taxpayer knowledge have a positive effect on tax revenue.